Advances in Kidney Preservation Techniques and Their Application in Clinical Practice. Issue 11 (November 2021) - Hosgood, Sarah A.; Brown, Rachel J.; Nicholson, Michael L.
Abstract : The use of cold preservation solutions to rapidly flush and cool the kidney followed by static cold storage in ice has been the standard kidney preservation technique for the last 50 y. Nonetheless, changing donor demographics that include organs from extended criteria donors and donation after circulatory death donors have led to the adoption of more diverse techniques of preservation. Comparison of hypothermic machine perfusion and static cold storage techniques for deceased donor kidneys has long been debated and is still contested by some. The recent modification of hypothermic machine perfusion techniques with the addition of oxygen or perfusion at subnormothermic or near-normothermic temperatures are promising strategies that are emerging in clinical practice. In addition, the use of normothermic regional perfusion to resuscitate abdominal organs of donation after circulatory death donors in situ before cold flushing is also increasingly being utilized. This review provides a synopsis of the different types of preservation techniques including their mechanistic effects and the outcome of their application in clinical practice for different types of donor kidney.